Antibiotic prescribing knowledge, awareness, and attitude of dental surgeons practicing in the urban Indian population - Rathi Rela (Wolters Kluwer Medknow Publications, 2021)
Background: Studies have reported that dental procedures may serve as a portal of entry for bacteria into the blood circulation, commonly termed as bacteremia which may inhabitate the heart and joints subjected to repair and replacement by prosthesis and may lead to complications in immunocompromised patients. Dental procedure may play a pivotal role in the development of infective endocarditis and infection around the prosthetic joint. Antibiotic use is suggested for all dental procedures requiring gingival manipulation or of the periapical region of teeth or mucosal incision in these patients. Objective: The present study has been conducted to inspect the antibiotic prescribing practices of general dentists among 250 dental practitioners. Methods: The study was conducted on 250 dental surgeons practicing in the urban Indian population of various parts of the country. A validated questionnaire was developed by a multidisciplinary dental and medical team and was circulated on the subject of the basic knowledge and awareness about antibiotic prophylaxis in susceptible patients. The data from the participants were collected, collated, and statistically analyzed. Results: The present study comprised 250 dental surgeons; 178 out of 250 were male, whereas 72 were female. Antibiotic prophylaxis guidelines were followed by 169 practitioners (67.60%), whereas 81 (32.40%) dentists did not follow any guidelines. Out of 169, 67 followed the American Academy of Orthopaedic Surgeons (AAOS) guidelines (39.64%), 58 followed American Heart Association (AHA) guidelines (34.30%), whereas 44 followed general physician's guidelines (26.03%). On screening the underlying conditions for which antibiotic cover was prescribed, it was shown that majority of the dental surgeons did the same for patients with cardiac valve repair or replacement (230; 92%), followed by infective endocarditis (212; 84.80%); organ transplant (212; 84.405); diabetes (189; 75.60%); prosthetic joint replacement (150; 60%); and congenital heart defect (110; 44%). Conclusion: Patients should then be trained to perform meticulous oral hygiene and advised to schedule regular dental checkups to maintain optimal dental health. Dentists should use antibiotic prophylaxis in only conditions associated with a valid scientific basis and should follow the standard protocols recommended by the American Dental Association, AHA, or AAOS.